The Indigenous Knowledge of Illuminated Boat Procession of the Thai-Lao Ethnic Group in Mekong Sub-region - Intirard, Pinit; Kanajakit, Sombat; Phanurat, Achara; Udomthawee, Kunnika Jitakoom (Richtmann Publishing, 2012)
The research design was mixed methods of quantitative and qualitative approaches. The qualitative research was In-Dept Interview with 60 peoples comprised 40 Thais, and 20 Laos and quantitative research was survey research with 520peoples of Thai-Lao ethnics group who involved in Illuminated Boat Procession (IBP). The content from qualitative research wasanalyzed to construct the questionnaire for quantitative research. Factor analysis was used for determination the componentfactors. The objectives of this research were to study conservation of Buddhism Srikotrabun culture relate to IBP and to analyzecomponent factor of conserving IBP of Thai-Lao Ethnic Group in Mekong Sub-region. The results indicated that ten factors wereas the followings: 1) Indigenous wisdom of IBP is secret codes for merit-making, and a knowledge center of three worlds(heaven, human and nether). 2) Local hydrographic knowledge related to geographical knowledge through practices of the LordBuddha’s worship and the ancestral worship. 3) The art of IBP passed from generation to generation via fundamental education.4) Illuminated boat body of fire knowledge based on light and water that reflect dharma principles in human realm, the universe,god realm and the river god. 5) Physical knowledge of earth, water, air, and fire that related to the elimination of misery existed inall three realms: heaven, human and hell. 6) The lighted boat engineering and technology are wisdom related to aquatic plantand animal ecology. 7) During the festival, it is believed that motherhood and living creatures were born from the theories ofphysical science and wind folklore. 8) IBP is similar to the energy and chemical circulation in the living creatures’ food chain. 9)IBP refers to philosophy and practices related to beliefs associated with Karma in Spirituality, Brahmanism, and Buddhism, andto protect ethnic and ecosystem. 10) The lighted boat construction is the procedure of merit practice, forgiving, and sacrificingconnected to intellectual pathway.